Automation in garment manufacturing - Nayak, Rajkishore; Padhye, Rajiv (Duxford Woodhead Publishing, 2018)
Automation in Garment Manufacturing provides systematic and comprehensive insights into this multifaceted process. Chapters cover the role of automation in design and product development, including color matching, fabric inspection, 3D body scanning, computer-aided design and prototyping. Part Two covers automation in garment production, from handling, spreading and cutting, through to finishing and pressing techniques. Final chapters discuss advanced tools for assessing productivity in manufacturing, logistics and supply-chain management. This book is a key resource for all those engaged in textile and apparel development and production, and is also ideal for academics engaged in research on textile science and technology.--Provided by publisher.
Introduction to automation in garment manufacturing -- Automation versus modeling and simulation -- Automation in production of yarns, woven, and knitted fabrics -- Automation in fabric inspection -- Artificial intelligence and its application in the apparel industry -- Automation in spreading and cutting -- Automation in material handling -- Application of robotics in garment manufacturing -- Automation in sewing technology -- 3D body scanning -- Computer-aided design: garment designing and patternmaking -- Advancements in production planning and control -- Use of advanced tools and equipment in industrial engineering -- automation in quality monitoring of fabrics and garment seams -- Recent developments in the garment supply chain.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Textile industry -- Automation; Electronic books